Stability simulation analysis of targeted puncture in L4/5 intervertebral space for PELD surgery - Liu, Yuhuai; Zhang, Qiongchi; Ji, Ning; Wang, Jie; Li, Jie; Du, Jinpei; Zhao, Jinghao; Ouyang, Pengrong; Qin, Jie; Li, Haopeng; Wang, Dong (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction The application prospects of percutaneous endoscopic lumbar discectomy (PELD) as a minimally invasive spinal surgery method in the treatment of lumbar disc herniation (LDH) are extensive. This study aims to find the optimal entry angle for the trephine at the L4/5 intervertebral space, which causes less lumbar damage and has greater postoperative stability. To achieve this, we conduct a three-dimensional simulated analysis of the degree of damage caused by targeted puncture-based trephine osteotomy on the lumbar spine. Methods We gathered clinical CT data from patients to construct a lumbar model. This model was used to simulate and analyze the variations in trephine osteotomy volume resulting from targeted punctures at the L4/5 interspace. Furthermore, according to these variations in osteotomy volume, we created Finite Element Analysis (FEA) models specifically for the trephine osteotomy procedure. We then applied mechanical loads to conduct range of motion (ROM) and von Mises stress analyses on the lumbar motion unit. Results In PEID, the smallest osteotomy volume occurred with a 20° entry angle, close to the base of the spinous process. The volume increased at 30° and reached its largest at 40°. In PTED, the largest osteotomy volume was observed with a 50° entry angle, passing through the facet joints, with smaller volumes at 60° and the smallest at 70°. In FEA, M6 exhibited the most notable biomechanical decline, particularly during posterior extension and right rotation. M2 and M3 showed significant differences primarily in rotation, whereas the differences between M3 and M4 were most evident in posterior extension and right rotation. M5 displayed their highest stress levels primarily in posterior extension, with significant variations observed in right rotation alongside M4. Conclusion The appropriate selection of entry sites can reduce lumbar damage and increase stability. We suggest employing targeted punctures at a 30° angle for PEID and at a 60° angle for PTED at the L4/5 intervertebral space. Additionally, reducing the degree of facet joint damage is crucial to enhance postoperative stability in lumbar vertebral motion units.